The Aolministrative Structure (ministerial) established in Irap in1959 - يوسف, سرمد سعد (lark, 2018)
The administrative system in Iraq in 1959 witnnessed significant changes in The level of its organizational and functional structure and its economic and service functions ,and to high light the most important  administrative (ministerial) deveiopmwnts in the economic and service in the history of contemporary Iraq , the researchers specialized in this study , which focused on the joints of the structure of the structure of the Iraq state created after afull year of the revolotion of 14 july 1958 , the subject of the topic is asked for three parts and an introduction and a conclusion , the first part dealt with  the historical back ground of the  structure of the administrative (ministerial) in  Iraq before 1959 , the second part dealt with  the study of the administrative (ministerial) economic structure that was introduction in 1959. The third part covered the administrative (ministerial) structure of  service that was introduced in the same year .